Greece : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2003)
The Report on the Observance of Standards and Codes (ROSC) Data Module provides a review of Greece's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS), complemented by the in-depth assessment of the quality of Greece's national accounts, consumer price index (CPI), producer price index (PPI), and government finance, monetary, and balance-of-payments statistics (BOP). The assessment was carried out by a mission from the IMF Statistics Department. Finally, this study provides recommendations to achieve improvements in Greece's statistics.